Employee motivation as a predictor of organizational competitiveness of Nigerian bottling firms - Enyinna, Ugwu Kelechi; Ogbonna , Ofor George; Odinakachi, Njoku Charles (YAYASAN MITRA PERSADA NUSANTARA, 2023)
This study focused on employee motivation and organizational capabilities of Nigerian Bottling Firms, South-East. The study adopted correlational survey design and questionnaire as instrument for data collection. The total population of the study comprised of 610 participants from the cadre of senior level managers, middle level managers, and lower-level staff/subordinates of the firm. The sample size was determined using Taro Yamane formula and calculated as 242. Simple random sampling technique was adopted in the distribution of the survey. Out of 242 questionnaires administered only 226 were filled and returned while the remaining 16 were not utilized for the study. The results of hypothesis confirmed a strong correlation between employee motivation and organizational competitiveness. The data collected from the field survey are limited to Owerri and Enugu production plant. The researchers contribute to knowledge in the literature through the use of new concepts in the research objective, use analytical tool, industry of study and geographic coverage. The researchers recommend managers to routinely re-evaluate their organizational strengths and weaknesses and work with the human resources department to fill competency shortages. The researchers developed a mathematical model representing employee commitment and organizational capabilities in the methodology.